Multiplicity of Solutions for Neumann Problems for Semilinear Elliptic Equations - Yu-Cheng An; Hong-Min Suo (Abstract and Applied Analysis)
Using the minimax methods in critical point theory, we study the multiplicity of solutions for a class of Neumann problems in the case near resonance. The results improve and generalize some of the corresponding existing results.